Congenital Anomalies in Yemeni Newborns: A Retrospective Study at a Tertiary Care Hospital in Sana’a City - Sahar A. Thabet; Ahmed S. Hudna; Abdulrahman M. Alhadi; Hala Al-Kherbash (University of Science and Technology, Sana’a, Yemen, 2024)
Background: Congenital anomalies (CAs) are major causes of morbidity and mortality among newborns worldwide. Therefore, the present study aimed to determine the prevalence and types of CAs in Sana’a city, Yemen. Methods: This retrospective, cross-sectional study was conducted among newborns admitted to Al-Thawra Modern General Hospital in Sana’a from January to December 2017. Data were collected from 1100 medical records of newborns, besides data about their mothers, using a predesigned data collection sheet. Data were then analyzed, and the results were presented as frequencies and proportions. Results: Of 1100 newborns, 164 (14.9%; 95% confidence interval: 12.9–17.1) newborns had CAs. Of these, 74.4% had single-system CAs, and 25.6% had multiple-system CAs. Gastrointestinal tract anomalies (43.9%) were the most frequent CAs, followed by anomalies of the central nervous system (CNS) (18.9%), musculoskeletal system (17.1%), chromosomes (15.2%) and cardiovascular system (14%). However, orofacial anomalies of cleft lip and cleft palate (2.4%) were the least frequent CA, followed by urogenital anomalies (8.5%). Esophageal atresia (33.3%) and imperforated anus (25%) were the most frequent gastrointestinal CAs. On the other hand, meningocele (35.4%) was the most frequent CNS anomaly. Of musculoskeletal anomalies, limb defects were the most frequent (96.4%), while achondroplasia was observed among 3.6% of newborns with CAs. Congenital heart disease was the most frequent cardiovascular anomaly (95.7%), while dextrocardia was observed among 4.3% of newborns. Hypospadias (57.2%) was the most frequent urogenital anomaly, followed by ureteropelvic junction obstruction (21.5%). More than half of newborns with CAs died, while 35.4% of them were discharged from hospital without correction of CAs. On the other hand, CAs were corrected for 11.6% of newborns before discharge. Conclusion: The prevalence of CAs among Yemeni newborns is relatively high and can be observed in more than one in ten newborns. The majority of CAs usually affect a single system, most frequently affecting the gastrointestinal tract, followed by the CNS, musculoskeletal system, chromosomes and cardiovascular system. Half of newborns with CAs usually die in hospital before discharge. Therefore, it is necessary to educate parents and conduct regular antenatal screening by a pediatrician to detect these anomalies and manage them appropriately and in a timely manner.